PERAN ZINC TERHADAP JUMLAH LEUKOSIT PADA JARINGAN KULIT PASCA INSISI TIKUS Sprague Dawley YANG DIBERI PAKAN LEMAK TINGGI - , WULANDARI; , Drh.Rr.Devita Anggraeni, MP., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Skin wounds are common, however the duration of recovery for each animal is different. Many factors impede the wound healing process, either comes from within the body or outside the body, one of which is obesity. The assumption that fat animals are always healthy is not always true, because it often ends in case of overweight or even obese. Provision of zinc are known to accelerate the wound healing process. Monitoring of wound healing can be done by examine the infiltration of inflammatory cells in the wound area. This study was aimed to determine the effect of topical zinc the number of leukocytes in skin tissue injury of the rats given high fat diet. This study was used 32 Sprague Dawley rats which were given high fat diet. After 2 months of treatment, the rats were incised on the back and were given topical zinc. The skin around the wound were taken on the first and third day post-incision for histopathological preparations the number of leukocytes around the incision area were calculated. The number of leucocytes was analyzed using ANOVA factorial (2x2x2), while histopatological analysis was done descriptively. The result showed that there was significant interaction between diet and topical zinc (P < 0,05). It was concluded that administration of zinc in rats with high fat diet affects the number of leukocytes in tissue injury.